1994
DOI: 10.1007/bf00022161
|View full text |Cite
|
Sign up to set email alerts
|

Combining abilities of in vitro traits in wheat (Triticum aestivum L.) immature embryo cultures

Abstract: Combining ability for six in vitro culture traits in wheat were studied in a 8 x 8 diallel cross (excluding reciprocals) . Specific combining ability effects (sca) were significant for all six traits derived from immature embryos on two media protocols, whereas general combining ability (gca) variances were significant only for five of them. Furthermore, based on ratios obtained by comparing the ratio of K2 gca to K 2 sca, sca was more important than gca for all six traits . Genetic correlations between shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…This suggested that both additive and non-additive genetic variance may contribute to the genetic expression of immature embryo culture traits. These results are supported by other findings by Barakat (1994) and Abd El-Maksoud (2003).…”
Section: Resultes and Discussionsupporting
confidence: 92%
“…This suggested that both additive and non-additive genetic variance may contribute to the genetic expression of immature embryo culture traits. These results are supported by other findings by Barakat (1994) and Abd El-Maksoud (2003).…”
Section: Resultes and Discussionsupporting
confidence: 92%
“…Therefore, shoot formation ability in immature embryo cultures of wheat may be under different genetic control. Recently, Barakat (1994) reported that dominance or dominant types of epistasis may play a role in the immature embryo culture response to in vitro culture traits.…”
Section: Generation Meansmentioning
confidence: 99%
“…The genetic aspects of plant regeneration are generally considered important, but have been less widely studied. Examination of a dialled cross among eight wheat cultivars has provided evidence that both additive and non-additive variations are operating to control the in vitro culture traits, but non-additive gene action predominates (Barakat, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A main part of biotechnology application that mediates crops genetic manipulation and serves in plant breeding is regeneration of plants from cells and plant parts via tissue culture. Haplodization, somaclonal variation, cell suspension culture, protoplasts and DNA delivery techniques remain the key approaches of tissue culture to regenerate plant breeding materials (Barakat and Cocking, 1989, Barakat, 1994, Henry et al, 1994Barakat, et al 2017). The expected outcomes of these technologies are increased genetic variation in addition to saving time.…”
Section: Introductionmentioning
confidence: 99%